'Cult' Rhetoric in the 21st Century: Deconstructing the Study of New Religious Movements - Thomas, Aled (Religion at the Boundaries Series, 2024)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Contributors -- Foreword: Introduction to the Religion at the Boundaries series -- Acknowledgements -- Part I: Approaches to 'cult' rhetoric -- Chapter 1: 'Cult' rhetoric in the twenty-first century: The disconnect between popular discourse and the ivory tower -- Chapter 2: Balancing pragmatism and precision: Inform's approach to cult rhetoric -- Chapter 3: A history of anticult rhetoric -- Chapter 4: The paradigm shift from sacred to profane -- Chapter 5: The dangerous cult exercise: Popular culture and the ongoing construction of the new religious threat -- Chapter 6: The recognition of cults -- Part II: Contemporary 'cultic' studies -- Chapter 7: The light of the world: La Luz del Mundo, liminality and NRM studies -- Chapter 8: Cults of conspiracy and the (ongoing) Satanic Panic -- Chapter 9: 'There is no QAnon': Cult accusations in contemporary American political and online discourse -- Chapter 10: Playing at religion: Understanding contemporary spiritual experiences in popular culture -- Chapter 11: Attempting to educate journalists about the role of cult essentialism in the Branch Davidians-federal agents conflict -- Afterword: Responses and conclusions -- Index.